2017
DOI: 10.3892/ol.2017.5888
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a functions as a potential tumor suppressor through directly targeting CDC42 in non-small cell lung cancer

Abstract: Abstract. The expression and function of microRNA-29a (miR-29a) have been investigated in various types of cancer. In the present study, the expression, function and underlying molecular mechanism of miR-29a were investigated in non-small cell lung cancer (NSCLC). The expression level of miR-29a in NSCLC was determined using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Cell proliferation, migration and invasion ability were determined using Cell Counting Kit-8, cell migration and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…MiR-29a was claimed to have the ability to decreased proliferation in non-small-cell lung cancer (NSCLC), via negatively correlating with LIM and SH3 domain protein 1 (LASP1), a cAMP- and cGMP-dependent signaling protein and a member of the nebulin family of actin-binding proteins [ 50 ]. At the same time, the suppression of proliferation caused by miR-29a was also affirmed by Li et al [ 51 ] partly via targetting cell division control protein 42 homolog (CDC42) in NSCLC. In addition, Pei et al [ 52 ] demonstrated that, in BCa cells, miR-29a could induce cell proliferation by directly targetting ten eleven translocation (TET) 1 (TET1).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…MiR-29a was claimed to have the ability to decreased proliferation in non-small-cell lung cancer (NSCLC), via negatively correlating with LIM and SH3 domain protein 1 (LASP1), a cAMP- and cGMP-dependent signaling protein and a member of the nebulin family of actin-binding proteins [ 50 ]. At the same time, the suppression of proliferation caused by miR-29a was also affirmed by Li et al [ 51 ] partly via targetting cell division control protein 42 homolog (CDC42) in NSCLC. In addition, Pei et al [ 52 ] demonstrated that, in BCa cells, miR-29a could induce cell proliferation by directly targetting ten eleven translocation (TET) 1 (TET1).…”
Section: Introductionmentioning
confidence: 73%
“…Also, miR-29a diminished cell migration partly by directly targetting MCL1 in PCa [ 77 ]. MiR-29a functioned as an inhibition role in NSCLC via negatively modulating expression of LASP1 [ 50 ] and CDC42 [ 51 ], LASP1 functioned as a cAMP- and cGMP-dependent signaling protein and CDC42 was a protein involved in the adjustment of the cell cycle. MiR-29a , directly under-regulating VEGF-A, was identified to inhibit the tumor microvessel density, and then suppressing the invasion and metastasis of GC cells [ 78 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have shown that miRNAs are involved in regulating various biological processes, including development, cell proliferation, differentiation, apoptosis, metabolism and signal transduction (14)(15)(16). Multiple bodies of evidence have indicated that miRNAs are abnormally expressed in almost all types of human cancer (17)(18)(19). Current studies have acknowledged that more than half of miRNAs are located in cancer-related genomic regions; this finding suggests that dysregulation of miRNAs plays important roles in carcinogenesis and cancer progression (20).…”
Section: Introductionmentioning
confidence: 99%
“…Cdc42 may function as molecular switches and signals in multicellular pathways influencing various biological responses such as motility, morphology, and gene expression. [ 77 ] Overexpression of cdc42 has also been found in many human cancers such as lung cancer, [ 78 ] CRC, [ 79 ] and breast cancer. [ 80 ] Several studies indicated deregulation of cdc42 induced cellular transformation through disturbing the activity of Ras and epidermal growth factor receptor [ 81 ] and promoted cell migration by mediating fibroblast growth factor and vascular endothelial grown factor.…”
Section: Discussionmentioning
confidence: 99%